1995
DOI: 10.1113/jphysiol.1995.sp020533
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of power output and muscle metabolites following 30 s of maximal sprint cycling in man.

Abstract: 1. The recovery of power output and muscle metabolites was examined following maximal sprint cycling exercise. Fourteen male subjects performed two 30 s cycle ergometer sprints separated by 1-5, 3 and 6 min of recovery, on three separate occasions. On a fourth occasion eight of the subjects performed only one 30 s sprint and muscle biopsies were obtained during recovery. 2. At the end of the 30 s sprint phosphocreatine (PCr) and ATP contents were 19-7 + 1'2 and 70 5 + 6-5% of the resting values (rest), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
299
3
17

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(347 citation statements)
references
References 36 publications
28
299
3
17
Order By: Relevance
“…However, possible differences in VO 2 fluctuations across exercise modes needs to examined in future studies. Although many factors influence the concentration of lactate in the blood, the steady increase in blood lactate levels found here may indicate an incomplete resynthesis of PCr and thereby increasing requirements from lactic anaerobic energy together with the aerobic energy sources utilized (Bogdanis et al 1995). Several studies have shown correlations between the decrement in RSA and the decline in intramuscular pH (Glaister 2005;Edge et al 2006).…”
Section: Physiological Responsesmentioning
confidence: 68%
“…However, possible differences in VO 2 fluctuations across exercise modes needs to examined in future studies. Although many factors influence the concentration of lactate in the blood, the steady increase in blood lactate levels found here may indicate an incomplete resynthesis of PCr and thereby increasing requirements from lactic anaerobic energy together with the aerobic energy sources utilized (Bogdanis et al 1995). Several studies have shown correlations between the decrement in RSA and the decline in intramuscular pH (Glaister 2005;Edge et al 2006).…”
Section: Physiological Responsesmentioning
confidence: 68%
“…It has been previously observed that within two minutes of rest 50% of the depleted intramuscular phosphocreatine stores can be replenished (Bogdanis, Nevill, Lakomy and Boobis, 1998). As the rest periods prescribed between sets of ISRR loading were 130 seconds in duration, it would appear possible that similar repletion rates may have occurred in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…NMES which uses medium frequency alternating current induces vasodilation & increase peripheral blood flow [46,47] & the suction system with an electrode has a massage effect [27]. Also the rest position during NMES favors the resynthesis of PCr [25]. The calf muscles stimulated in this study are largely responsible for venous return [48] and may have aided a better recovery.…”
Section: Discussionmentioning
confidence: 89%
“…Low frequency electrical stimulation is the commonly used mode for the recovery process because it induces light muscle contraction responsible for muscle pump effect & therefore enhanced muscle blood flow. NMES also favors the resynthesis of phosphocreatine [25]. In addition, a decrease in heart rate suggests that efficient blood flow stimulation by NMES can alleviate the stress placed on the heart [26].…”
Section: Introductionmentioning
confidence: 98%